1994
DOI: 10.1007/bf02355680
|View full text |Cite
|
Sign up to set email alerts
|

Influence of motivational centers of the hypothalamus on the functioning of the visual area of cerebral cortex

Abstract: It has been demonstrated in chronic experiments on awake rabbits that a solitary stimulation of the middle hypothalamus, its ventromedial and lateral nuclei (VMN and LN), exerts a phasic effect on a formation of the primary response of the visual cortex evoked by a test light flash. In the initial period of their action, the hypothalamo-cortical responses (1-43 msec for the VMN and 1-10 msec for the LN) completely inhibit the formation of the response of the visual cortex to the light stimulus, while in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The LH innervated by the Ce also innervates autonomic cell groups in the brainstem and spinal cord (Saper et al, 1976;Barbas et al, 2003), suggesting that LH may play an important role in initiating autonomic responses that accompany conditioned fear (LeDoux et al, 1988). Some other studies suggested that the VMH is involved in the motivational behaviour (Gadzhieva & Dmitrenko, 1994;Etgen & Morales, 2002). Thus, the CREB activation seen in the amygdala and hypothalamus might be critical for TWAA memory processing.…”
Section: Discussionmentioning
confidence: 99%
“…The LH innervated by the Ce also innervates autonomic cell groups in the brainstem and spinal cord (Saper et al, 1976;Barbas et al, 2003), suggesting that LH may play an important role in initiating autonomic responses that accompany conditioned fear (LeDoux et al, 1988). Some other studies suggested that the VMH is involved in the motivational behaviour (Gadzhieva & Dmitrenko, 1994;Etgen & Morales, 2002). Thus, the CREB activation seen in the amygdala and hypothalamus might be critical for TWAA memory processing.…”
Section: Discussionmentioning
confidence: 99%